Community Participation of the “Kampung KB” Program: Study in Malang City Year 2020 - Ekawati, Rany; Deniati, Ema Novita; Hapsari, Anindya; Mutakifah, Lu'luim; Annisaa, Annisaa; Ariyanti, Lilik (citeus, 2024)
Indonesia has a significant population problem. The national population grows by a staggering 4.5 million people annually, and Malang is one example of a city experiencing this rapid growth. The government is implementing a program called